RIP CURRENTS SIGNATURES ZONE DETECTION ON ALOS PALSAR IMAGE AT IJARANGTRITIS BEACH, INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Having bay and gulf morphology as cresentic beach. Parangtritis coast has been known potentially threat by rip currents hazard. This study aims to identifj' and detect breaking waves region and surf zone on ALOS PALSAR images. and identifY and extract the cove shape shoreline morphology of Parangtritis beach. ALOS PALSAR Fine Beam Single (FBS) HH polarization acquired on 2/1dMay 2007 and 171hJUI/e 2007, oj}' nadir angle 34.3°, and in descending mode level 1.0 were utilized to derive amplitude information using Sigmasar. Shoreline mOlphology detection showed that the cusps system has not changed much during May to June 2007 when PALSAR images acquired, but might have shifted individually. The use of optical sensor with the same spatial resolution, ALOS A VNIR-2. supports to distinguish the boundary and determine the shoreline mOlphology of Paral/gtritis beach. Keywords: ALaS PALSAR, breaking waves, rip currents, shoreline morphology, surf zone, Parangtritis, Indonesia